Stakeholder Engagement and Quality Health Care Service Delivery in Government Hospitals. A Case of Lyantonde Hospital - Kyomuhangi, Fatuma; Muriisa, Roberts; Kansiime, Noel Kiiza (International Journal for Multidisciplinary Research (IJFMR), 2024)
This study examines the impact of stakeholder involvement on the quality of healthcare service delivery in government hospitals in Lyantonde District, Uganda. The main issue identified is the subpar quality of healthcare services in the district, which is attributed to a lack of adequate stakeholder engagement in the planning, implementation, and monitoring and evaluation (M&E) processes. The study, employing a case study design, involved 257 respondents, including hospital administration, doctors, nurses, Local Council Leaders, the District Health Officer (DHO), a Biostatistician, the Lyantonde Hospital Management Committee, and patients. Data were collected using questionnaires, interviews, and documentary reviews, analyzed through SPSS and content analysis. A key finding is that while stakeholders like local leaders and district officials are actively involved, there is a significant lack of direct engagement from community members and patients, particularly in planning and M&E processes. The study recommends enhancing community involvement through structured consultations and participatory approaches to improve healthcare service delivery. The conclusion underscores that addressing the gaps in stakeholder engagement is crucial for improving the quality of healthcare services and ensuring that community needs are effectively met.